Study of the Productivity of Oil Palm Plants (Elaeis guineensis Jacq.) on Different Topographies - Ingrid Ovie Yosephine; Zulham Effendi; Dewi Fitriana (The University of Lampung, 2025)
The productivity of oil palm plants is influenced by several factors, including the environment (soil and climate), genetics (type or variety of oil palm) and agronomic techniques that are able to support the growth of oil palm to achieve optimal production. The objective of this research was to study the effect of topography on the oil palm productivity. Purposive sampling was carried out through direct observation in the field at three different topographies, namely, flat-to-undulating, hilly, and hilly without terraces. Each topography consisted of 2 blocks with 30 samples each. The total number of samples was 180 trees of Dy×P Dumpy variety with the same planting years, namely 2006. The results showed that oil palm plants did not show significant differences in term agronomic characteristic. The productivity of oil palm plants planted in flat to undulating topography was 21.23 ton/ha, higher than those of hilly topography (17.09 ton/ha) and those of hilly without terraces (14.62 ton/ha). Agronomic characters that were positively correlated with bunch weight were plant height, stem diameter, and number of bunches (in flat-to-undulating lands); all agronomic characters in hilly land; and plant height and number of fronds in hilly land without terraces